A susceptor with a ∧-shaped slot in a vertical MOCVD reactor by induction heating - 李志明 李海玲 甘小冰 江海鹰 李金屏 付小倩 韩延彬 夏英杰 尹建芹 黄艺美 胡仕刚 (Journal of semiconductors, 2014)
By using the numerical simulation for the temperature field in the metal organic vapor deposition （MOCVD） reactor by induction heating, it is found that the temperature distribution in the conventional cylinder-shaped susceptor is nonuniform due to the skin effect of the induced current, which makes the temperature distribution of the wafer nonuniform. Therefore, a novel susceptor with a A-shaped slot is proposed. This slot changes the mode and the rate of the heat transfer in the susceptor, which improves the uniformity of the temperature distribution in the wafer. By using the finite element method （FEM）, the susceptor with this structure for heating a wafer of four inches in diameter is optimized. It is observed that the optimized susceptor with the A-shaped slot makes the uniformity of the temperature distribution in the wafer improve by more than 85%, and a good uniformity of temperature distributions is kept under different wafer temperatures, which may be beneficial to the film growth.